Melatonin Mitigates Salt Stress in Wheat Seedlings by Modulating Polyamine Metabolism - Ke, Qingbo; Ye, Jun; Wang, Bomei; Ren, Jianhong; Yin, Lina; Deng, Xiping; Wang, Shiwen (Frontiers in Plant Science, 2018)
Melatonin, a small molecular weight indoleamine molecule, is involved in various biological processes and responses to environmental cues in plants. However, its function in abiotic stress response and the underlying mechanisms is less clear. In this study, we investigated the effect of melatonin on wheat seedlings growth under salt stress condition. Exogenous melatonin pretreatment partially mitigated the salt-induced inhibition of whole-plant growth as judged from shoot dry weight, IAA content, leaf photosynthesis rate, maximum photochemistry efficiency of photosystem II, and chlorophyll. The mitigation was also observed in reduced accumulation of H2O2 in melatonin-pretreated wheat seedlings exposed to salt stress. Exogenous melatonin increased endogenous melatonin content by evaluating the levels of TaSNAT transcript, which encodes a key regulatory enzyme in the melatonin biosynthetic pathway. Furthermore, melatonin increased polyamine contents by accelerating the metabolic flow from the precursor amino acids arginine and methionine to polyamines; melatonin also decreased the degradation of salt-induced polyamines. Taken together, these results provide the evidence that melatonin mitigates salt stress mainly through its regulation on polyamine metabolism of wheat seedlings.